Solubilization of lipids from hamster bile-canalicular and contiguous membranes and from human erythrocyte membranes by conjugated bile salts. - Graham, J M (1987)
We have demonstrated in vitro the efficacy of the taurine-conjugated dihydroxy bile salts deoxycholate and chenodeoxycholate in solubilizing both cholesterol and phospholipid from hamster liver bile-canalicular and contiguous membranes and from human erythrocyte membrane. On the other hand, the dihydroxy bile salt ursodeoxycholate and the trihydroxy bile salt cholate solubilize much less lipid. The lipid solubilization by the four bile salts correlated well with their hydrophobicity: glycochenodeoxycolate, which is more hydrophobic than the tauro derivative, also solubilized more lipid. All the dihydroxy bile salts have a threshold concentration above which lipid solubilization increases rapidly; this correlates approximately with the critical micellar concentration. The non-micelle-forming bile salt dehydrocholate solubilized no lipid at all up to 32 mM. All the dihydroxy bile acids are much more efficient at solubilizing phospholipid than cholesterol. Cholate does not show such a pronounced discrimination. Lipid solubilization by chenodeoxycholate was essentially complete within 1 min, whereas that by cholate was linear up to 5 min. Maximal lipid solubilization with chenodeoxycholate occurred at 8-12 mM; solubilization by cholate was linear up to 32 mM. Ursodeoxycholate was the only dihydroxy bile salt which was able to solubilize phospholipid (although not cholesterol) below the critical micellar concentration. This similarity between cholate and ursodeoxycholate may reflect their ability to form a more extensive liquid-crystal system. Membrane specificity was demonstrated only inasmuch as the lower the cholesterol/phospholipid ratio in the membrane, the greater the fractional solubilization of cholesterol by bile salts, i.e. the total amount of cholesterol solubilized depended only on the bile-salt concentration. On the other hand, the total amount of phospholipid solubilized decreased with increasing cholesterol/phospholipid ratio in the membrane.